Pengaruh Penerapan Model Pembelajaran Project-Based Learning Berbantuan Perplexity AI Terhadap Motivasi dan Hasil Belajar Siswa Pada Mata Pelajaran IPS di kelas IX SMP Muhammadiyah 2 Taman Sidoarjo - RATU AYU PUTRI HARIYANTO (Jurnal Dialektika Pendidikan IPS, 2026)
This study aims to examine the effect of implementing the Project-Based Learning (PjBL) model assisted by the Perplexity AI application on students’ motivation and learning outcomes in Social Studies (IPS). The research employed a quantitative approach with a quasi-experimental design using a non-equivalent control group design. The research subjects were class IXA as the experimental group and IXD as the control group at SMP Muhammadiyah 2 Taman Sidoarjo. The research instruments included a motivation questionnaire and learning achievement tests (pre-test and post-test). Data analysis using the Independent Sample T-Test showed a significance value (Sig. 2-tailed) of 0.000 < 0.05, indicating a significant difference between the experimental and control groups in both motivation and learning outcomes. The average post-test score for the experimental class was 85.1, and the motivation score reached 71.8. These findings indicate that the implementation of PjBL assisted by Perplexity AI has a positive effect on improving students’ motivation and learning outcomes.